Gêneros textuais no processo de alfabetização em turma do 1º ano de ensino fundamental - SILVA, Suziane Thais Martins da (2018)
This paper aims to investigate in what way the teachers of public schools on the outskirts of Belém-PA use the genres in language literacy of students and discuss the possible contributions of the use of this feature. The discussion on literacy and genres was built based on studies of Cagliari (2002), Soares (2004), Marcuschi (2002) and others. The collaborators of the research were two teachers who worked in class the first year of elementary school. This research can be characterized as a qualitative case study. Used for the construction of the information the results of interviews, field diary and textual productions of the students. From the teachers' responses analysis was carried out one confrontation of observations in the classroom and the textual productions of students. In the testimonies of the teachers and the students' productions it is possible to identify significant progress in learning to present an objective textual genres. We conclude that the implementation classes that put motivating situations for students and with different methodologies can be configured in excellent learning opportunities for students in the early years, as well as provide the professional development of current and future teachers who engage in such an undertaking.